Health professionals’ perceptions of strategies in prevention and caring of intrafamily violence in a southern Brazilian - Manfrini, Gisele Cristina; Gatti de Andrade , Larissa Vitória; Artioli, Giovanna; Andrade dos Santos, Manuela (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: to identify interdisciplinary practices and care technologies in the health care network in the capital of Santa Catarina, and the assistance instruments and strategies used by professionals and teams in caring for families in situations of violence. Methods: qualitative study, with twelve professionals who work in the Municipal Health Network, in Florianópolis, accessed through the snowball method. Data collection took place from March 2022 to July 2023, through semi-structured interviews and qualitative thematic analysis. Results: two categories emerged: assistance strategies in approaching families in situations of intrafamily violence and care technologies for vulnerabilities, described and discussed based on the literature. Conclusions: caring for families in situations of violence is complex and demands interdisciplinary work, which, for different reasons, may not occur in an ideal way. Still, it is possible to identify the development of care plans and prevention strategies that target the issue of violence, as well as the use of light technologies.